La aplicación de los medios alternativos de solución de controversias en los reclamos en contra de las compañías de seguros en la ciudad de Guayaquil - Morán Soriano, María Fernanda (2019)
Alternative means are one of the forms of peaceful settlement of disputes, which is enshrined in the Charter of the United Nations, which in Ecuador includes these postulates and in the Constitution of 2008 in its Article 190. Facts, like the excessive number of judgments that are processed in the judiciary, the delay in the solution of the lawsuits, the cost of the process, the lack of professional ethics and of an adequate academic preparation of the majority of the judges, the submissive dependence of the judicatures to political stores , the corruption that corrodes all the estates of the judicial system, are those that have caused Arbitration and Mediation to be considered as a better solution to conflicts than through ordinary justice….